The Yield of Ten-Year T-Bonds: Stumbling Towards a 'Good' Forecast - Rafael Weißbach; Vladyslav Ponyatovskyy; Guido Zimmermann (Universität Dortmund, Sonderforschungsbereich 475 - Komplexitätsreduktion in Multivariaten Datenstrukturen, 2006)
Due to their status as "the" benchmark yield for the world's largest government bond market and its importance for US monetary policy, the interest in a "good" forecast of the constant maturity yield of the 10-year U.S. Treasury bond ("T-bond yields") is immense. This paper assesses three univariate time series models for forecasting the yield of T-bonds: It shows that a simple SETAR model proves to be superior to the random walk and an ARMA model. However, dividing the sample of bond yields, dating from 1962 to 2005, into a training sample and a test sample reveals the forecast to be biased. A new bias-corrected version is developed and forecasts for March 2005 to February 2006 are presented. In addition to point estimates forecast limits are also given.
Keywords: C52; E47; 519; T-bond; times series; 10-year yield; TAR model; bias-correction; non-linear time series